Sustainable management of bud rot disease of coconut - Prathibha, VH; Daliyamol; Rajkumar; Hegde , Vinayaka; Chandran , Kp (Bangladesh Journal of Botany, 2023)
Bud rot incited by Phytophthora palmivora Butl. is a fatal disease in coconut. Different fungicides were tested under in vitro condition and highly effective fungicides were selected for evaluation under field condition to develop IDM strategies against bud rot. All the fungicides and Trichoderma coir pith cake significantly reduced the bud rot disease incidence compared to the control. Five fungicides were highly effective for three consecutive years. Chlorothalonil 78.12 WP was found cost effective in the management of bud rot disease and Trichoderma coir pith cake could be used for eco-friendly management of the disease. Bangladesh J. Bot. 52(3): 749-753, 2023 (September)